Preparation of biomass‐derived phosphorus‐doped microporous carbon material and its application in dye adsorption and CO2 capture. (26th April 2022) - Wu, Ren; Hang, Yongping; Li, Jinhao; Bao, Agula
Abstract : Microporous P‐doped carbon materials are synthesized by a pyrolysis method using MCM‐22 as a template, sucrose as a precursor, and phosphoric acid as phosphorus sources. The results show that the pore structure of the carbon materials can be adjusted by changing the amount of phosphoric acid and template. When the P/C molar ratio is 0.075, the obtained P‐doped microporous carbon material shows excellent specific surface area up to 621 m 2 /g and shows a high adsorption capacity of 199.40 mg/g for crystal violet dye, with a removal rate of 98.9%. When testing the CO2 adsorption capacity, it was found that the maximum adsorption capacity reached 63 mg/g and remained stable after 10 adsorption and desorption cycles, with excellent cycle stability. The adsorption obeys pseudo‐second‐order kinetic model, and the adsorption isotherm follows the Langmuir model.